ANALISIS KINERJA KEUANGAN DAN KINERJA SAHAM SEBELUM DAN SESUDAH RIGHT ISSUE (STUDI EMPIRIS PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA 2008-2010) - Panca Fransiskus Simanullang; Daljono Daljono (Diponegoro Journal of Accounting, 2014)
Right issues are the additional public offerings of a company’s shares beyond the initial public offerings, in order to generate extra financing for business expansion, the expansion of investment, improve the capital structure or fulfillment of its liability, etc. Financial performance is measured by four financial ratios, they are debt to equity ratio (DER), return on assets (ROA), current ratio (CR), and price to book value (PBV). While the stock performance is measured using stock returns.The samples of this research are the manufacturing firms listed in Indonesian Stock Exchange in 2008 -2012. The samples are collected using purposive sampling method and resulted 40 firms become the samples.The results showed that right issue bring a netral impact or an average in the ratio of ROA, CR, and PBV. Right issue has no impact on DER and stock returns, which the DER has increased as a equity post right issue. Right issue leads to an increase in stock returns in the second year after the right issue, but the overall stock return declined an average post-right issue. Although results vary, but generally the rise and decline is so small that it does not have a significant impact on changes in financial performance  and stock performance  after the right issue. It can be concluded that the issuance of right issue, financial performance and stock performance has not changed as indicated by the results of research that  is not  affected significantly